Building Eco-Territorial Movements in Private-Community Conservation Areas: The Case of the Chaparrí Nature Reserve in Lambayeque - Flores-Fernandez, Vera Alejandra (2024)
Nature conservation is an urgent issue globally, particularly regarding its integration with sustainable socio-economic development. In Latin America, countries like Peru face increasing tensions between nature conservation and neoextractivist models. The eco-territorial turn of socio-environmental movements in the region reflects a critique of this economic model and seeks collective governance of the territory. In this context, Private Conservation Areas (PCAs) have proliferated in recent decades, with the Chaparrí Nature Reserve pioneering as the first private-community PCA led by a peasant community. The case of Chaparrí illustrates the struggle between local conservationists and proponents of extractivist development. This article explores the eco-territorial movement generated in Chaparrí from the activist research that brought together efforts with Belgian and Peruvian academics and students. The eco-territorial movement in Chaparrí has not only catalyzed transformations in community dynamics but also collaborations with a wide range of actors. The scholars from the activist research managed to integrate into the landscape of actors and institutions revolving around Chaparrí, opening new and innovative opportunities for collaboration.